Knowledge, attitudes and practices related to antimicrobial use and resistance among fish farmers in Dar es Salaam, Tanzania - Zainabu Hamisi Kilusungu; Zuhura Idd Kimera; Wilson Nandolo; Peter Kunambi; Fauster Mgaya; Mecky Isaac Matee; Daud Kassam (PLoS ONE, 2025)
This study was conducted in Dar es Salaam, Tanzania, the major commercial city of Tanzania, to assess the knowledge, attitudes, and practices (KAP) of fish farmers on antimicrobial use (AMU) in aquaculture. This was a cross-sectional study conducted between March and June 2023, involving total of 60 fish farmers. Data were collected electronically using the Afya-Data application and analysed with SPSS Version 26.0. The findings showed that most farmers were male (71.7%), over 50 years of age (51.7%), and college-educated (38.3%). However, 80% had not received formal aquaculture training, and 50% lacked access to aquaculture extension services. While 80% of the respondents were aware of antibiotics and 93% were familiar with antimicrobial resistance (AMR), only 35% demonstrated a positive attitude towards the use of antimicrobial agents. Although no farmer reported direct antibiotic use, potentially risky practices were noted. These included the use of treated manure for pond fertilization in 38.3% of farms and irregular pond drainage into the environment practices that can contribute to the spread of AMR beyond aquaculture settings. To address these gaps, we recommend strengthening aquaculture extension services with a focus on improved pond management practices, establishing a functional fish disease surveillance system, and enhancing collaborative research among government, academic, and research institutions. The Department of Aquaculture Extension should develop cost-effective farmer-to-farmer extension models. To improve access to information, we also propose forming small cooperative groups under the Aquaculture Association of Tanzania (AAT). Moreover, the Ministry of Livestock and Fisheries (MLF) should develop and implement clear guidelines for monitoring AMU, AMR, and fish diseases, both existing and emerging.